Application fields of wood as a renewable energy source in Europe - Csatári, Nándor (Acta Agraria Debreceniensis, 2012)
Fuelwood, and wood wastes provide almost half of the renewable energy production of the European Union. Enhancing the use of wood in renewable energy production has more constraint than wind- or solar energy. Forests in the EU member states are sustainably used, they are increasing both in terms of area, and growing stocks. There are possibilities to enhance the fallings and use more fuelwood. Short rotation coppices could fulfill the long term demand for fuelwood; because these plantations surpass the dendromass yield of forests.